Keramahan untuk Berjalan : Perspektif Dari Lingkungan Setempat di Bandar Lampung, Indonesia - Akhmad Baiquni Muhaemin (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Walking is inherently a human activity, and has been related to many benefits including health, social, economy, and transportation, but there are still gaps from the western dominated literature to the local context of Indonesia. This research aims to understand the parameters of walkability from a short walk by people preferences from its origin focusing in a selected neighborhood of Kemiling Sub District in Bandar Lampung city. Data collection consists of building a basis of walkability parameters from literature of walking and walkability and identifying the local walkability parameters by synchronizing the data based on in depth adult interviews. Comparing the literature analysis resulted to five possible categories of barriers in the neighborhood: feasibility, destination, safety, comfort, and design quality. In the case of Bandar Lampung, locals probably perceived walking as more casual affairs with no expectation to the quality of their environment while accepting comfort as the most important barriers rather than safety.